High-yield fabrication of DNA and RNA constructs for single molecule force and torque spectroscopy experiments - Papini, Flávia S.; Seifert, Mona; Dulin, David (Nucleic Acids Research, 2019)
Single molecule biophysics experiments have enabled the observation of biomolecules with a great deal of precision in space and time, e.g. nucleic acids mechanical properties and protein-nucleic acids interactions using force and torque spectroscopy techniques. The success of these experiments strongly depends on the capacity of the researcher to design and fabricate complex nucleic acid structures, as the outcome and the yield of the experiment also strongly depend on the high quality and purity of the final construct. Though the molecular biology techniques involved are well known, the fabrication of nucleic acid constructs for single molecule experiments still remains a difficult task. Here, we present new protocols to generate high quality coilable double-stranded DNA and RNA, as well as DNA and RNA hairpins with ∼500-1000 bp long stems. Importantly, we present a new approach based on single-stranded DNA (ssDNA) annealing and we use magnetic tweezers to show that this approach simplifies the fabrication of complex DNA constructs, such as hairpins, and converts more efficiently the input DNA into construct than the standard PCR-digestion-ligation approach. The protocols we describe here enable the design of a large range of nucleic acid construct for single molecule biophysics experiments.
CRIS-Team Scopus Importer:2019-12-20